2012
DOI: 10.1038/ejcn.2012.139
|View full text |Cite
|
Sign up to set email alerts
|

Acute effect of oral water intake during exercise on post-exercise hypotension

Abstract: BACKGROUND/OBJECTIVES: Post-exercise hypotension (PEH) is a sustained reduction in mean arterial blood pressure (MAP) after prolonged exercise. As water drinking is known to elicit a large acute pressor response, we aimed to explore the effect of drinking water during exercise on PEH. SUBJECTS/METHODS: Ten normotensive male volunteers performed the control protocol: 30 min supine rest, 60 min cycling exercise in moderate intensity, and 60 min supine rest recovery. In the water drinking protocol, the same proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…However, in a recent study, Endo et al (2012) showed that WI during exercise can prevent hypotension in the postexercise period. It seems likely, therefore, that the greater parasympathetic reactivation after WI may be a compensatory response to a raised blood pressure at this time.…”
Section: Discussionmentioning
confidence: 96%
“…However, in a recent study, Endo et al (2012) showed that WI during exercise can prevent hypotension in the postexercise period. It seems likely, therefore, that the greater parasympathetic reactivation after WI may be a compensatory response to a raised blood pressure at this time.…”
Section: Discussionmentioning
confidence: 96%
“…PAEH has been demonstrated as clinically relevant because it is significant in magnitude and is sustained for a prolonged period after exercise (3). Moreover, it has been reported in different populations, including individuals who are hypertensive (4-9), prehypertensive (10,11), and normotensive (5,12-30). …”
Section: Introductionmentioning
confidence: 99%
“…Some of them attribute PAEH to reduced cardiac output (CO) (6,9,12,15,19,21-24,30-34), while others report a peripheral vascular resistance (PVR) reduction (4,7,16-18,20-23,25-29,33-53). This controversy suggests that some other factors could influence these determinants.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, there is a lack of studies investigating the influence of water intake on the postexercise pressure response. In a literature review, we found only one study conducted by Endo et al 8 that evaluated the effect of water intake on BP during the recovery period. The authors observed that ad libitum water intake during exercise prevented the reduction in postexercise SBP and DBP.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have shown that water intake promotes an increase in BP through sympathetic activation 7 , a response that may inhibit PEH. In this respect, Endo et al 8 investigated the effects of water intake on postexercise BP responses and observed the absence of PEH. However, the subjects were submitted to exercise of moderate intensity.…”
Section: Introductionmentioning
confidence: 99%